Association between age-related macular degeneration and subjective cognitive complaints. Issue 9 (4th December 2019) - Zhu, Zhuoting; Liao, Huan; Wang, Wei; Scheetz, Jane; Zhang, Jian; He, Mingguang
Abstract : Purpose: To investigate the association between age-related macular degeneration (AMD) and subjective cognitive complaints (SCCs) in the USA. Methods: A total of 5604 participants aged 40 years and older from the 2005–2008 National Health and Nutrition Examination Survey were included. Retinal photography was graded into no AMD, early and late AMD based on the modification of the Wisconsin Age-Related Maculopathy Grading System. SCCs were based on the self-reported difficulty in remembering or confusion. Sample weights were used to generate nationally representative data. Multivariate regression analyses were used to assess the association between AMD severity and SCCs, controlling for potential confounders. Results: Participants with any AMD had higher prevalence of SCCs relative to participants without AMD (6.8% vs 13.6%, p<0.001). After adjusting for potential confounding factors, presence of any AMD was significantly associated with 1.62-fold higher odds of having SCCs (95% CI 1.16 to 2.27, p=0.007). Similarly, participants with early (OR 1.58; 95% CI 1.14 to 2.17, p=0.007) and late AMD (OR 2.02; 95% CI 1.08 to 3.79, p=0.030) were also associated with elevated odds of reporting SCCs after controlling for confounders. Conclusions: We found significant associations between AMD severity and SCCs in this US population. More attention should be paid on the subjective memory function and potential risk of cognitive decline among patients with AMD.